Structure and distribution of palm tree species in Altingia excelsa planted forest in Gunung Gede Pangrango National Park, West Java, Indonesia - ASEP SADILI; ANDI SALAMAH; EDI MIRMANTO; KUSWATA KARTAWINATA (Biodiversitas Journal of Biological Diversity, 2024)
Abstract. Sadili A, Salamah A, Mirmanto E, Kartawinata K. 2024. Structure and distribution of palm tree species in Altingia excelsa planted forest in Gunung Gede Pangrango National Park, West Java, Indonesia. Biodiversitas 25: 249-256. Gunung Gede Pangrango National Park (GGPNP) is a conservation area consisted of natural forest and planted forest, including Altingia excelsa Noronha stands which were planted in 1925. As a result of secondary succession, various plants grow under Altingia excelsa stands, including palm tree species (Arecaceae). This research was conducted to determine the structure, population, and distribution patterns of palm trees in Altingia excelsa planted forest in Bodogol Resort, GGPNP. The data were collected by establishing a one-hectare plot divided into 100 subplots of 10 m × 10 m. Palm tree species with a Diameter at Breast Height (DBH) ?3 cm were measured, and the tree heights were estimated. Data analysis included Relative Dominance (RDo), Relative Density (RDen), Relative Frequency (RF), Importance Value Index (IVI), Shannon Wiener Diversity Index (H'), Evenness Index (E), Index of Dispersion (ID), analysis of variance values (S2) and Chi-square analysis (Q). The study results recorded four species from three genera of Arecaceae which consisted of 171 trees with a total Basal Area (BA) of 0.63 m2/ha. Pinanga coronata (Blume ex Mart.) Blume was the most dominant palm tree species with IVI of 156.89%), followed by Pinanga sp. (IVI=72.04%), Caryota rumphiana Mart. (IVI=55.77%), and Arenga pinnata (Wurmb) Merr. (IVI=15.38%). In term of diameter class distribution, Pinanga coronata and Pinanga sp. were regenerating well. Spatial distribution patterns of Arenga pinnata, Caryota rumphiana, and Pinanga sp. were regular, while Pinanga coronata was clustered. Periodical studies in the future to determine the mortality and natality of the palm trees are recommended to understand the dynamics of vegetation succession.